Education and credit: A Matthew effect - Manthos D. Delis; Yota D. Deli; José-Luis Peydró; Adele Whelan (University College Dublin, UCD School of Economics, 2022)
Using a unique corporate loans dataset for entrepreneurs with small and microenterprises, this paper examines how educational attainment affects bank credit decisions and subsequent individual and firm outcomes. Our results highlight a "Matthew Effect," where an initial advantage is self-amplifying. We find that entrepreneurs who obtain university education are more likely to apply for credit, and receive higher credit scores, and better lending terms. Via this credit channel, such entrepreneurs have significantly better future firm outcomes compared to those without a university education. Furthermore, we find a key role for investments in innovation, intangible assets, and lower within-firm pay inequality.
Keywords: G21; G32; I23; I24; I26; 330; Education; Credit; Higher education; Loan application; Bank credit decisions; Firmperformance; Pay Inequality